Back Cover: Synthesis and Mechanistic Study of Cyclic Oxoguanidines via Zn(OTf)2‐Catalyzed Guanylation/Amidation from Readily Available Amino Acid Esters and Carbodiimides (Chem. Eur. J. 29/2015). Issue 29 (13th July 2015) - Chi, Yue; Xu, Ling; Du, Shanshan; Yan, Haihan; Zhang, Wen‐Xiong; Xi, Zhenfeng
<x xml:space="preserve">Abstract</x> The Zn(OTf)2‐catalyzed guanylation/amidation from readily available amino acid esters and carbodiimides has been achieved. In their Full Paper on page 10369 ff., W.‐X. Zhang and co‐workers describe the synthesis of various cyclic oxoguanidines. It is the first time that an ammonium salt has been used in the guanylation reaction. The two reagents′ structures are shown on the tail of the stone fish, and they meet Zn(OTf)2 to yield an important zinc intermediate, the structure of which is shown on the head of the fish. This whole fish is like a machine to spray the cyclic oxoguanidine products, which means it is a cheap and cheerful reaction. This background picture is the famous view of Peking University.